The Delivery of Extracellular “Danger” Signals to Cytosolic Sensors in Phagocytes - Gonzales, Gerone A.; Canton, Johnathan (Frontiers in Immunology, 2022)
Phagocytes, such as macrophages and dendritic cells, possess the relatively unique ability to ingest large quantities of exogenous material into membrane-bound endocytic organelles such as macropinosomes and phagosomes. Typically, the ingested material, which consists of diverse macromolecules such as proteins and nucleic acids, is delivered to lysosomes where it is digested into smaller molecules like amino acids and nucleosides. These smaller molecules can then be exported out of the lysosomes by transmembrane transporters for incorporation into the cell’s metabolic pathways or for export from the cell. There are, however, exceptional instances when undigested macromolecules escape degradation and are instead delivered across the membrane of endocytic organelles into the cytosol of the phagocyte. For example, double stranded DNA, a macromolecular danger associated molecular pattern shed by necrotic tumor cells, is endocytosed by phagocytes in the tumor microenvironment and delivered to the cytosol for detection by the cytosolic “danger” sensor cGAS. Other macromolecular “danger” signals including lipopolysaccharide, intact proteins, and peptidoglycans can also be actively transferred from within endocytic organelles to the cytosol. Despite the obvious biological importance of these processes, we know relatively little of how macromolecular “danger” signals are transferred across endocytic organelle membranes for detection by cytosolic sensors. Here we review the emerging evidence for the active cytosolic transfer of diverse macromolecular “danger” signals across endocytic organelle membranes. We will highlight developing trends and discuss the potential molecular mechanisms driving this emerging phenomenon.